2022
DOI: 10.1002/cphc.202200004
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Redox Properties of Pyridinium Appended 1,2‐Dithienylcyclopentenes

Abstract: The optical and redox properties of a methyl pyridinium appended 1,2-dithienylethene photochromic derivative have been thoroughly investigated. A complex multi-step photo/ redox mechanism is proposed for the closed isomer on the ground of spectro-electrochemical and theoretical data. The generated compounds are not stable over the time because of chemical reactions associated to the redox processes and a new dithienylethene derivative incorporating a seven-membered ring has been isolated and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Following the literature data, such a photochromic dicationic ligand is expected to exhibit two isomers: open and closed ones. Moreover, as shown previously for DTE pyridinium derivatives, the reduction of the closed form should lead to two other stable forms, that is, the corresponding radical cation and the neutral molecule, allowing a system that may exhibit four stable states . In addition, it was shown that the reduction of the open isomer induces a ring-closure electrocyclization process, as already described for DTE pyridinium derivatives .…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…Following the literature data, such a photochromic dicationic ligand is expected to exhibit two isomers: open and closed ones. Moreover, as shown previously for DTE pyridinium derivatives, the reduction of the closed form should lead to two other stable forms, that is, the corresponding radical cation and the neutral molecule, allowing a system that may exhibit four stable states . In addition, it was shown that the reduction of the open isomer induces a ring-closure electrocyclization process, as already described for DTE pyridinium derivatives .…”
Section: Introductionsupporting
confidence: 65%
“…Moreover, as shown previously for DTE pyridinium derivatives, the reduction of the closed form should lead to two other stable forms, that is, the corresponding radical cation and the neutral molecule, allowing a system that may exhibit four stable states. 29 In addition, it was shown that the reduction of the open isomer induces a ring-closure electrocyclization process, as already described for DTE pyridinium derivatives. 30 The two coordinating terpyridine units ensure the formation of supramolecular polymers assembled in solution through the spontaneous formation of bis-terpyridine transition-metal complexes ([Fe(tpy) 2 ] 2+ ).…”
Section: ■ Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…The closed-to-open isomerization is triggered under visible light irradiation. [30][31][32][33][34][35] Due to the varied conjugation, a superhigh A closed/open = N (578 nm) is calculated for DAE, indicating the high efficiency of backward photoisomerization induced by visible light. Moreover, compared with that of Azo, slight conformation changes exist during the isomerization (1.1 Å on horizon and 0.7 Å on vertical).…”
Section: Diaylethene (Dae)mentioning
confidence: 99%